2004
DOI: 10.1038/sj.leu.2403391
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine arabinoside induces costimulatory molecule expression in acute myeloid leukemia cells

Abstract: Chemotherapeutic drugs kill cancer cells mainly by direct cytotoxicity, but they might also induce a stronger host immune response by causing the tumor to produce costimulatory cell surface molecules like CD80. We previously reported that in myeloid leukemic cells, c-irradiation induced CD80 expression. In this study, we show that cytosine arabinoside (Ara-C), even at low doses, induced CD80 expression in vitro in mouse DA1-3b leukemic cells, by a mechanism that involved reactive oxygen species. In vivo experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…In addition, mouse leukemic cells exposed in vivo to Ara-C were more susceptible to CTL-mediated cell killing (Vereecque et al, 2004). This result suggests that the specific antileukemic activity of CTL, acting in synergy with enhanced sensitivity of leukemic cells to immune-mediated cell killing induced by chemotherapy, might eradicate minimal residual disease (van der Most et al, 2009).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, mouse leukemic cells exposed in vivo to Ara-C were more susceptible to CTL-mediated cell killing (Vereecque et al, 2004). This result suggests that the specific antileukemic activity of CTL, acting in synergy with enhanced sensitivity of leukemic cells to immune-mediated cell killing induced by chemotherapy, might eradicate minimal residual disease (van der Most et al, 2009).…”
Section: Discussionmentioning
confidence: 54%
“…The B7-CD28 signaling pathway is the most potent co-stimulatory pathway facilitating antigen-specific T-cell activation. An assay of human acute myelocytic leukemia cells demonstrated that exposure to doses of Ara-C as low as 0.05 mM led to a marked increase of CD86 and a lesser increase of CD80 (Vereecque et al, 2004). Most of specimens showed enhanced expression of CD80 or CD86, but some subtypes of acute myelocytic leukemia, especially FAB M0 and M1, showed no modification or a decrease of expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanisms aside from mAb blockade have also been investigated by several groups for modulating B7-H1 expression indirectly using IFN-g, CXCL10, and alternative methods. 76,80,85,113,114 Furthermore, combination therapy of B7-H1 blocking mAb along with a costimulatory CD137 mAb enhanced tumor regression. 72 In a recent model by Geng et al, 115 B7-H1 blockade with soluble PD-1 in combination with an HSP70 vaccine increased T H 1 cytokines and antitumor immunity in a murine lung metastasis model.…”
Section: Flies and Chenmentioning
confidence: 97%
“…[19][20][21] Marked expression of B7-H1 has been reported for various human carcinomas and in mouse models expression of B7-H1 enhances tumor growth and allows dormant tumor cells to escape from CTLs. 16,[22][23][24][25][26][27][28][29] Blocking B7-H1 enhances the effects of cancer vaccines. [30][31][32][33][34] Toll-like receptor (TLR) stimulation can also induce B7-H1 expression in mouse tumor cells.…”
Section: Introductionmentioning
confidence: 99%